PENGEMBANGAN MEDIA (PAKAPIN) PAPAN KANTONG PINTAR BERBASIS LITERASI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Ahmad Sholeh; Sri Cacik; Mega Puspita Sari; Gargarisna Diputra (Prodi PGSD Universitas PGRI Ronggolawe, 2022)
Technological developments have a negative impact on students' motivation and learning outcomes. Media Pakapin (Papan Kantong Pintar) literacy-based aims to increase student motivation and learning outcomes. The method used in the Pakapin media development research is the ADDIE model, namely Analysis, Design, Develop, Implement, and Evaluate. The research subject is in grade 4 elementary school. The research was carried out on 30 May 2022. The research instruments were interviews, observations, tests, and validations. The analysis technique used is validity test, practicality test, and effectiveness test. The results of media validation to expert validators, namely media experts and material experts to determine the feasibility of the media and obtained the results of the assessment from 2 validators with an average score of 4.6 so that the media was declared feasible. The results of the effectiveness of students were assessed from the results of the motivational assessment and question sheets with a final count system using the N-Gain technique, the score obtained a motivational result of 0.9 and student learning outcomes of 0.79 so that Pakapin media was declared effective. The results of practicality assessed by the appraiser obtained a result of 90 so that Pakapin media was declared practical. From the results of this research, it can be concluded that the development of literacy-based Pakapin media can affect the improvement of students' motivation and learning outcomes.